THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT, MINIMUM WAGES RATE AND EDUCATION ON EMPLOYMENT IN JAVA - Tantry, Arisyi Pamilie (Jurnal Ilmiah Mahasiswa FEB, 2017)
Indonesia is an archipelago country which more than a thousand islands. One of the islands is Java. Java is a densely populated that give a massive contribution in Indonesia economy. Even Java donated big amount of number in Gross Regional Domestic Product, the number of unemployment in Java still remains high. This research has purpose to understand about the effect of gross domestic regional product, minimum wages rate and education to the employment in Java from 2011-2015. The data used in this research is secondary data from Central Bureau of Statistics in Indonesia. This research contain 6 provinces in Java namely Jakarta, West Java, Banten, Yogyakarta, Central Java and East Java. The data processed with Eviews 7.0 with panel data estimation. The result of this study indicates that GRDP and Education have positive and significant effect on employment, while minimum wages rate has negative impact even there is significant effect to the employment in Java.Â Keywords: Gross Regional Domestic Product, Minimum Wages Rate, Education, Employment.